A Realist Philosophy of Economics - Karl Mittermaier (Bristol University Press, 2023)
EPUB and EPDF available Open Access under CC-BY-NC-ND licence. With contributions from Alan Kirman and Rod O'Donnell, Karl Mittermaier's posthumously published work establishes a conceptual framework that will help economic theorists explore new paths of empirical analysis.
Keywords: 330; Economic theory; Empirical; Facts; History of economic thought; Institutions; Preferences; Rational; Utility